PENERAPAN TGT BERBANTUAN BAMBOOZLE UNTUK MENINGKATAN HASIL BELAJAR PADA PEMBELAJARAN IPA - Nur Fitriyah; Mohammad Budiyanto (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
The learning outcomes of students at SMP 17 Surabaya show that most of them have not achieved the minimum competency standard based on observation results. Therefore, this study aims to improve student learning outcomes using TGT cooperative learning assisted by digital media. This study describes the implementation of learning, the improvement of cognitive learning outcomes, and student responses to the application of the Teams Games Tournament (TGT) cooperative learning model assisted by Bamboozle digital media on the subject of heat transfer. The type of research used is a pre-experimental design with a One Group Pretest-Posttest Design involving 30 students in class VII-E of SMP Negeri 17 Surabaya. The research instruments included observation sheets on learning implementation, tests, and response questionnaires. The learning outcome data were analyzed descriptively. The results showed that: (1) learning implementation was carried out very well, with a percentage of 95.55% in the first meeting and increased to 96.2% in the second meeting; (2) there was a significant difference in student learning outcomes, as indicated by a Wilcoxon test significance value of <0.001, and (3) student responses were classified as positive in the very high category, as indicated by an average questionnaire percentage of 92%. The conclusion of this study indicates that the Bamboozle-assisted TGT cooperative learning model can improve the learning outcomes of junior high school students.